2009
DOI: 10.1063/1.3116138
|View full text |Cite
|
Sign up to set email alerts
|

Quantified light-induced fluorescence, review of a diagnostic tool in prevention of oral disease

Abstract: Diagnostic methods for the use in preventive dentistry are being developed continuously. Few of these find their way into general practice. Although the general trend in medicine is to focus on disease prevention and early diagnostics, in dentistry this is still not the case. Nevertheless, in dental research some of these methods seem to be promising for near future use by the general dental professional. In this paper an overview is given of a method called quantitative light-induced fluorescence or (QLF) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
20

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 37 publications
0
24
0
20
Order By: Relevance
“…1,5 Several tools proposed to support the clinicians in caries diagnosis process are based on the quantification of the fluorescence emitted by the carious tissue. 2,7 Another use of these devices is the possibility of quantifying the red fluorescence of dental plaque in the oral environment. 6,[8][9][10] One of those devices is the quantitative light-induced fluorescence (QLF), which emits a blue light at 405 nm and collects the fluorescence at the green and red spectra.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,5 Several tools proposed to support the clinicians in caries diagnosis process are based on the quantification of the fluorescence emitted by the carious tissue. 2,7 Another use of these devices is the possibility of quantifying the red fluorescence of dental plaque in the oral environment. 6,[8][9][10] One of those devices is the quantitative light-induced fluorescence (QLF), which emits a blue light at 405 nm and collects the fluorescence at the green and red spectra.…”
Section: Introductionmentioning
confidence: 99%
“…6,[8][9][10] One of those devices is the quantitative light-induced fluorescence (QLF), which emits a blue light at 405 nm and collects the fluorescence at the green and red spectra. 7 With regard to the dental plaque, the researchers have first focused on the investigation of individual microorganisms responsible for the emission of the red fluorescence. The authors observed that obligate anaerobic bacteria were the main source of red fluorescence, including microorganisms usually present in thicker plaque and in dentin caries lesions.…”
Section: Introductionmentioning
confidence: 99%
“…This difference between carious and sound sites are presented as percentage of increase of red fluorescence. 3,8,11,14 Therefore, these differences between the two devices can explain the different performance observed in our study.…”
Section: Discussionmentioning
confidence: 55%
“…Moreover, an objective method could be less influenced by examiner's experience than would visual inspection. 4 Considering that LFpen and QLF (red fluorescence measurement) are methods based on the fluorescence emitted by microorganisms present in the caries lesions, 9,11,15 and since active caries lesions are more infected than inactive ones, 16 this possibility would be plausible. The old version of the LF method used with different drying times had been tested for this purpose previously, 28 but this methodology was not compared with visual inspection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation